"I don't think they need any help with the formula": Examining elementary preservice teachers' responses to volume tasks. (17th April 2022) - Hong, Dae S.; Runnalls, Cristina
Abstract: The purpose of this study was to explore how elementary preservice teachers (PSTs) responded to students' hypothetical misconceptions about volume measurement. We carried out both pre‐assessments and follow‐up interviews with 17 PSTs, with tasks focused on both volume content knowledge and hypothetical student responses to volume tasks. Preliminary findings indicated a preference toward show‐and‐tell responses, often with a focus correct or incorrect use of the volume formula. Although PSTs were frequently able to correctly identify students' learning challenges and make conceptual pedagogical suggestions with regards to volume, they experienced difficulty in addressing those challenges with more student—centered suggestions. Recommendations for supporting PSTs in teacher education programs are discussed.